Regional Science in a time of uncertainty - Bernard Fingleton (REGION, 2016)
I have given this paper the title 'Regional Science in a time of uncertainty' because that is what it appears to be, very much a time of uncertainty. Uncertainty is always with us, but what I mean is the future is more uncertain than usual. There are multiple unanticipated and threatening shocks to our economic, social and environmental systems. For example, global climate change appears to be upon us right now, so what is the future especially for the world's poorest people, living at the margins of existence? The after-effects of the 2007 shock to the global economy are still very much with us. In an era of very low demand, Central Banks are running out of policy options. We are moving into an era of experimental and unconventional fixes, such as negative interest rates. But these could have dangerous, unanticipated consequences. Also the upheavals in the Middle East are now being manifest as unforeseen mass migrations. Closer to home, the vote to exit the UK from the EU was based on a referendum dominated by claims and counterclaims about the effects of Brexit. Now the UK has voted to leave, the true consequences remain uncertain.
Keywords: 330; spatial econometrics; dynamic spatial panel model; simulation; European regional employment